Student readiness in the transfer of online learning to face-to-face learning after the Covid-19 Pandemic - Sumantri, Adhi; Palupi, Majang; Ping, Lim Cher (Program Pascasarjana Universitas Negeri Yogyakarta, 2023)
During the Covid-19 pandemic, many researchers flocked to examine students' readiness to participate in online learning. Furthermore, after the Covid-19 Pandemic, it provides motivation to examine the readiness of students in face-to-face learning after the Covid-19 Pandemic. This article aims to determine the readiness of students in changing online learning to face-to-face learning after the Covid-19 pandemic. This research is a mixed methods research, where strengthening the results of the research hypothesis using qualitative data from interviews with respondents selected based on certain criteria from the questionnaire results. The sampling technique used random sampling. The data for this study were obtained from filling out a questionnaire distributed to undergraduate students at two private universities and one state university in the city of Yogyakarta involving 172 respondents via Google Form. The data obtained was then processed through structural model evaluation with the SmartPLS application. Data collection was carried out through questionnaires and interviews to obtain qualitative data. Data validity tests were carried out using reliability, normality, and construct validity tests. Data were analyzed using a descriptive analysis model of structural evaluation or inner model and outer model. The results in this study found that there was no significant positive effect of institutional readiness on student readiness and there was a significant positive effect of learning experience on student readiness. This research is expected to trigger research with other similar themes that are better with a wider research object.